Effects of vestibular rehabilitation training combined with anti-vertigo drugs on vertigo and balance function in patients with vestibular neuronitis: a systematic review and meta-analysis - Chen, Jia; Liu, Zhixiang; Xie, Yulong; Jin, Song (Frontiers in Neurology, 2023)
Abstract Objective: To investigate the effects of vestibular rehabilitation training (VRT) combined with anti-vertigo drugs on vertigo and balance function in patients with vestibular neuronitis(VN). Data sources: PubMed, EMBASE, The Cochrane Library, Web of Science, CNKI, Wan Fang Data, VIP, and CBM were searched until July 13, 2023. Participants: Patients with vestibular neuronitis participated in the study. Results:21 studies including 1415 patients were included in this review for meta-analysis. According to the Physiotherapy Evidence Database (PEDro) quality assessment, four studies received high quality (≥seven scores) and seventeen studies received moderate quality (six scores). The meta-analysis showed that VRT combined with anti-vertigo drugs significantly reduced the Dizziness Handicap Inventory (DHI) score, the Vestibular Disorders Activities of Daily Living Scale(VADL) score and the Canal Paresis(CP) score, and improved the overall efficiency and the Berg Balance Scale (BBS) score, promoting vestibular evoked myogenic potentials(VEMPs) returned to normal in VN compared to simple anti-vertigo drugs or VRT alone. Conclusions: The results of this meta-analysis demonstrate the efficacy and safety of VRT combined with anti-vertigo drugs in patients with VN. Combined therapy can alleviate vestibular dysfunction such as vertigo and vomiting in patients, improve daily activity ability and balance ability, in addition to VRT has fewer adverse reactions, so it is extremely safe. However, there are shortcomings such as lack of long-term follow-up and different frequency and duration of treatment. Therefore, future randomized controlled trials(RCTs) with larger sample sizes and longer-term observations are needed to verify the effectiveness of VRT in combination with anti-vertigo drugs for VN.